2015
DOI: 10.1039/c5tc03396a
|View full text |Cite
|
Sign up to set email alerts
|

Charge trapping behavior visualization of dumbbell-shaped DSFXPY via electrical force microscopy

Abstract: The electrons and holes are injected into the sterically hindered organic semiconductor film (DSFXPY, 1,6-di(spiro[fluorene-9,90-xanthene]-2-yl)pyrene) through applying controllable biases on the conductive atomic force microscopy tip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Chotsuwan and Blackstock visualized the charge trapping process of single, multicharged polyamines via KPFM, as shown in Figure a. [ 78 ] By KPFM, injection and retention processes of trapped charges in the sterically hindered organic semiconductor films (1,6‐di(spiro[fluorene‐9,90‐xanthene]‐2‐yl)pyrene) (DSFXPY), [ 42 ] spiro[fluorene‐9,7‐dibenzo[ c , h ]acridin‐5‐one] (SFDBAO), [ 43 ] and tris (8‐hydroxyquinoline) aluminum (Alq 3 ) thin films [ 44 ] were investigated. For example, the dependences of the peak potential and the area of the trapped charges for the Alq 3 film on the injection time are shown in Figure .…”
Section: The Properties Of Trapping Charges For Different Materials Bmentioning
confidence: 99%
See 4 more Smart Citations
“…Chotsuwan and Blackstock visualized the charge trapping process of single, multicharged polyamines via KPFM, as shown in Figure a. [ 78 ] By KPFM, injection and retention processes of trapped charges in the sterically hindered organic semiconductor films (1,6‐di(spiro[fluorene‐9,90‐xanthene]‐2‐yl)pyrene) (DSFXPY), [ 42 ] spiro[fluorene‐9,7‐dibenzo[ c , h ]acridin‐5‐one] (SFDBAO), [ 43 ] and tris (8‐hydroxyquinoline) aluminum (Alq 3 ) thin films [ 44 ] were investigated. For example, the dependences of the peak potential and the area of the trapped charges for the Alq 3 film on the injection time are shown in Figure .…”
Section: The Properties Of Trapping Charges For Different Materials Bmentioning
confidence: 99%
“…With the EFM/KPFM techniques, researchers have widely explored the charge trapping properties and acquired abundant experimental results. [ 16,40,42,44,46,47,55,57,60,69,70,79,87,101–103,106,112,117–121 ] Some groups have reported that charge injection is influenced by the hydrophilicity of films and the atmospheric moisture. [ 46,47,60,101–103 ] The effects of the injection time, [ 44,46,79,119 ] injection bias, [ 40,44,79,119 ] and the duration of the applied field [ 113 ] on the charge trapping processes have also been widely investigated.…”
Section: The Mechanism Of Injection and Decaymentioning
confidence: 99%
See 3 more Smart Citations